ON THE QUESTION OF EVALUATION AND IMPROVEMENT ACTIVITIES OF FOREIGN REPRESENTATIONS OF THE RUSSIAN FEDERATION SUBORDINATE ENTITIES - R. R. Gimatdinov; I. R. Nasyrov (Vestnik MGIMO-Universiteta)
International and foreign economic relations of the subordinate entities of the Federation are an important factor of the socio-economic development of the regions. While being implemented in the mainstream of a state foreign policy, they contribute to strengthening the relations of friendship and cooperation between Russia and foreign countries.Foreign representations of regions are widely used to promote international interests of subnational actors. Contribution of foreign representations to the development of external relations is analyzed in numerous articles on paradiplomacy. Among the most studied issues are motivation the opening of foreign missions, political and legal conditions of their activities. However, up to the present there was no analytical models for assessing the effectiveness of foreign missions and improvement their activities.Two mutually reinforcing approaches to solving the problem of increasing the efficiency of representative offices are suggested. First one is further development of indicative management and the second one is an adapted method of multi-criteria evaluation, which is used in the decision analysis. Both proposed approaches use performance indicators focused on the evaluation the variety of projects implemented by regional representations.Indicators and other content components of the described methods are specified using the experience of foreign representations of the Republic of Tatarstan. The proposed approach can be easily modified for representations of the other subordinate entities of the Russian Federation, which, despite of the diversity of organizational forms of activities, work in a common political and legal environment and solve problems of similar content.Stimulating effect is one of the main advantages of using target indicators. They are helpful in orienting missions to priority areas of cooperation. The method based on the multi-criteria rating of the representative offices’ activity focuses on the general assessment of their work. It is easy to use and gives measurable results.The proposed methods are of an applied nature and can be recommended to government bodies coordinating foreign representations of the regions.